Sosialisasi Mahasiswa dalam Proses Penguatan Nilai-Nilai Pancasila di Lingkungan Masyarakat - Sulianti, Ani; Isyuniandri, Dzaky; Anjarwati, Ani; Ningrum, Erika Fara Septia; Nisak, Indani Khoirun (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2023)
The fading of Pancasila values in social life, makes students to revive or provide reinforcement of Pancasila values through real work lecture activities. In this writing using the method of implementing this service is divided into three stages 1. implementation of activities 2. implementation 3. output. This writing activity aims to provide reinforcement of Pancasila values in a society that increasingly understands each of the Pancasila precepts. As well as the active role of students in strengthening Pancasila values as the basis for life guidelines in the life of society, nation and state.